KERJASAMA SEKOLAH DAN ORANG TUA DALAM MENGATASI PERILAKU MENYIMPANG SISWA KELAS VIII B - Nurhasanah, Nurhasanah; Sulistyarini, Sulistyarini; Ulfah, Mariah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out, "school collaboration and parents in overcoming the deviant behavior of class VIII B students". The research method used is descriptive method with a form of qualitative research. The source of this research data is primary data sources and secondary data sources. Data collection techniques used are observation, interview and documentation techniques. While the data collection tool used is an observation guide, interview guide and documentation. The analysis in this study was presented in a qualitative descriptive manner using informants as many as 4 people consisting of Deputy Principal of Student Section, Class VIII B, Parents and Students. The results of this study indicate a form of preventive school and parent cooperation, namely by inviting parents to school and advising students both at school and at home, repressive forms of school and parent cooperation, namely by giving reprimand and punishment, forms of cooperation between schools and people curative old by giving a summons to parents of students to school and suspensionKeywords: Cooperation, Deviant Behaviour, Parents, Schools